If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -10x + 45 = 2 + 4x + -12 Reorder the terms: 9 + 45 + -10x = 2 + 4x + -12 Combine like terms: 9 + 45 = 54 54 + -10x = 2 + 4x + -12 Reorder the terms: 54 + -10x = 2 + -12 + 4x Combine like terms: 2 + -12 = -10 54 + -10x = -10 + 4x Solving 54 + -10x = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 54 + -10x + -4x = -10 + 4x + -4x Combine like terms: -10x + -4x = -14x 54 + -14x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 54 + -14x = -10 + 0 54 + -14x = -10 Add '-54' to each side of the equation. 54 + -54 + -14x = -10 + -54 Combine like terms: 54 + -54 = 0 0 + -14x = -10 + -54 -14x = -10 + -54 Combine like terms: -10 + -54 = -64 -14x = -64 Divide each side by '-14'. x = 4.571428571 Simplifying x = 4.571428571
| z^13+3*z^10+3*z^7+z^4=0 | | 3(m+3)-3(m+2)-27(3m-1)-2(3m)= | | -2x+3y=8 | | 4(7c+5)= | | x^2+10x+13=0 | | 6m^2-13m-28=0 | | 6x+3x=4-5(2x-3) | | x^3-14x-20=0 | | (5x-9)(x+7)=0 | | x+2x+2x-5+25=80 | | 48x^2-4=0 | | 2(3p-x)-(-4+x)= | | 2y+4x=106 | | -1.42(3x-5)= | | 2x+4=21 | | 7coshx+8sinhx=1 | | 9+-5(9+2x)=2+4(-3+1x) | | 9-5(2x-9)=2+4(1x-3) | | 7x+3=27+5 | | 2x-11y=23 | | 56-4x=5x+23 | | 13-9x=44-16x | | 226-7x=38x+16 | | 5-9x=29-16x | | -81-9x=-37-8x | | -63-2x=9-10x | | 115-5x=22x+19 | | 13-10x=33-24x | | 2+9y=14 | | 4k+13=7-2k | | 2x+20=11x-70 | | u^2+7u-2=0 |